Zero power infrared sensing in 2D/3D-assembled heterogeneous graphene/In/InSe/Au. Issue 8 (16th February 2022) - Jang, Hanbyeol; Song, Yumin; Seok, Yongwook; Im, Heungsoon; Kim, Tae Hyung; Lee, Joo-Hyoung; Kim, Yong-Hoon; Lee, Kayoung
Abstract : The self-powered infrared sensors show outstanding performance, achieving a photoresponsivity of ∼8.5 A W −1 and a detectivity of ∼10 12 Jones. Abstract : Low- or self-powered infrared sensors can be used in a broad range of applications, including networking mobile edge devices and image recognition for autonomous driving technology. Here, we show state-of-the-art self-powered near-infrared (NIR) sensors using graphene/In/InSe/Au as a photoactive region. The self-powered NIR sensors show outstanding performance, achieving a photoresponsivity of ∼8.5 A W −1 and a detectivity of ∼10 12 Jones at 850 nm light. Multiple self-powered InSe photodetectors with different device structures and contacts were systematically investigated. In particular, the asymmetrically assembled graphene/In/InSe/Au vertical heterostructure offers a high built-in field, which gives rise to efficient electron–hole pair separation and transit time that is shorter than the photocarrier lifetime. The built-in potential across the InSe was estimated using the Schottky barrier height at each metal contact with InSe, obtained using density functional theory calculations. We also demonstrate InSe vertical field-effect transistors and provide an out-of-plane carrier mobility of InSe. Using the out-of-plane mobility and structural parameters of each device, the built-in field, drift velocity, and corresponding transit time are estimated.